C–H Bond Functionalization of 1, 4‐Benzoquinone by Silver‐Mediated Regioselective Phosphination and Amination Reactions. Issue 17 (3rd May 2017) - Chang, Yu‐Chang; Yuan, Pin‐Ting; Hong, Fung‐E
Abstract : The one‐pot synthesis of 2, 5‐bis(diarylphosphoryl)‐3, 6‐bis(arylamino)cyclohexa‐2, 5‐diene‐1, 4‐diones has been achieved by Ag I ‐mediated full C–H functionalization of 1, 4‐benzoquinone (BQ) through regioselective dual phosphination and amination reactions. BQ, diarylphosphine oxides [SPOs, Ar2 PH(=O)], and imines reacted to give the products under mild conditions. 1, 4‐Naphthoquinone (NQ) could also be used instead of BQ. When aniline was used instead of the corresponding imine, a lower yield of the desired product was obtained. In the absence of Ag2 CO3, hydrophosphinylation of the imine by the SPO occurred as a competitive side‐reaction. Ag I plays versatile roles in this reaction, as a mediator for facilitating the consecutive additions of Ar2 P(=O) – and aniline to the related β‐carbon atoms of BQ, as an oxidant of hydroquinone (HQ) intermediates to form the substituted BQ counterpart, and as an inhibitor of the hydrophosphinylation side‐reaction of the imine by the SPO. The X‐ray crystal structures of several new products have been determined. A reaction mechanism is also proposed based on the experimental results. Abstract : " Like reactions, unlike reactivities". N‐phenylimines, nitrogen‐directing substrates in transition‐metal‐catalyzed C–H activations, turn out to be precursors of anilines in the presence of Ar2 P(O)‐H and Ag2 CO3 . Thus, fully functionalized 1, 4‐benzoquinones have been obtained by unprecedented dual and regioselective C–P and C–N bond formations in Ag I ‐mediated one‐pot reactions.